Coffee tree (Coffea arabica L.) Response to limestone in soil with high aluminum saturation coffee-tree lime response in soil with high aluminum saturation - Mendonça, Sebastião Marcos de; Martinez, Herminia Emilia Prieto; Neves, Julio César de Lima; Guimarães, Paulo Tácito Gontijo; Pedrosa, Adriene Woods (Coffee Science - ISSN 1984-3909, 2008)
Although Coffea arabica L. is not particularly sensitive to Al toxicity, the species presents different tolerance among varieties. The varieties previously classified as sensitive, Catimor (232T15-PN- UFV 3880), moderately tolerant, Catuaí 99 (IAC 99) and Catuaí Vermelho (IAC 15), and tolerant, Icatu (IAC 4045), were evaluated under field conditions. They were subjected to four limestone levels: 0.0; 0.5; 1.0; and 1.5 times the limestone requirement (LR) calculated by the base saturation method, considering 70% as the saturation reference value. The shoot and root growth were evaluated after 23 and 34 months, respectively, and the concentrations of Ca, Mn, Zn and Cu in the leaf tissues after 34 months. The shoot development of the variety ‘UFV 3880’ was not affected by liming levels. For roots development, limestone doses from ranging 0.74 to 0.84 LR, provided the largest concentrations of Ca in the foliar tissues. ‘IAC 99’ presented the best shoot development with limestone doses from 0.25 to 0.54 LR, and the best root development with doses from 0.33 to 0.40 LR. ‘IAC 15’ had a linear increase of root length and root specific surface with the increase of the limestone doses, which caused root thinning and elongation. This suggests that this variety is more sensitive to soil Al saturation than the other tested varieties. The ‘IAC 4045’ presented the best shoot and root development with liming ranging from 1.06 to 1.14 LR. It seems that other soil constraints, such as Mn content, impaired this variety development in lower limestone doses. Aluminum soil saturation up to 30 % in the superficial soil layer did not interfere in the development of the roots and shoots of the tested varieties.